A study on the rights of paediatric patient in medical negligence cases in Malaysia / Zairudin Hashim, Nur 'Aliaa Ahmad Mazuvil and Norashikin Abd. Halim - Hashim, Zairudin; Ahmad Mazuvil, Nur 'Aliaa; Abd. Halim, Norashikin (Faculty of Law, 2009)
The cases pertaining to medical negligence towards pediatric patients in Malaysia are showing a growing trend with regards to the number. The aim of this research is to study whether the laws have provided sufficient protection to these pediatric patients. Also, the study will look on the principles and provisions which the court used in deciding cases regarding medical negligence, The literature review (Chapter 2) will provide information on the rights of the pediatric patients in the case of medical negligence in Malaysia. This is based by reviewing several sources such as law reference books, newspaper reports, articles and journals. The legal chapter (Chapter 3) will try to determine whether pediatric patients are given the same rights as that of normal (adult) patient. In relation to that, defects of the law as connected to this issue will be explored. On the finding chapter (Chapter 4) of the report, the field works deal with a respondent and some investigation and deductions derived from his perceptions on the matters relating to the rights of the pediatric patients. The central argument of this study will discuss on whether the laws have provided sufficient protection to these pediatric patients.